Gender, Time Use, and Models of the Household - Apps, Patricia (World Bank, Washington, DC, 2013)
The aim of this paper is to explain why time use data are essential for analyzing issues of gender equity and the intra-household allocation of resources, comparing living standards, and estimating the behavioral effects of changes in policy variables. The first step in the exposition is to show that the neglect of these data in much of the literature on household behavior, in both developed and developing economies, can be traced to unrealistic assumptions on domestic production and the mistaken idea that non-market time can be viewed as leisure. It is argued that an approach is required that makes explicit the need for data on the time family members spend on domestic work as well as on labor supply. An approach of this kind is outlined and used to identify the specialized assumptions that are employed when they are missing. The paper also discusses the limitations of available time use survey datasets that are due to deficiencies in survey design. The more serious and common problems are illustrated using as case studies the Statistics South Africa 2000 Time Use Survey and the time use module included in the Nicaraguan 1998 Living Standards Measurements Survey.